Restoration of boreal wetlands increases bat activity - Vasko, Ville (John Wiley and Sons Inc, 2025)
Wetlands are important habitats for insectivorous bats, as the presence of water promotes insect abundance and provides drinking water for wildlife, and therefore could promote bat conservation. Research on bats and wetlands has mainly focused on constructed wetlands, and with a geographical emphasis on eastern United States and central Europe, whereas relatively little is known about the effects of wetland restoration on bats, especially in the boreal zone. We conducted a Before-After-Control-Impact (BACI) study in 21 wetlands. Using acoustic survey techniques, we collected information on bats both before and after restoration, with 7 of the 21 wetlands acting as control sites and 14 as impact (i.e., restored) sites. Acoustic surveys were conducted in May–September in the years 2018, 2019 (before restoration) and in 2021 and 2022 (after restoration). Species detection for each night was assessed by automated analysis of audio recordings. We assessed the presence and number of active minutes of the Northern bat (Eptesicus nilssonii) and the Myotis species group, using a generalized linear mixed model. Wetland restoration increased the acoustic activity of both taxa, but not their presence. Thus, restoration increased the usage of wetlands as a feeding site for bats. Our BACI study provides strong evidence that wetland restoration caused an increase in bat activity, and can be used as an effective tool for bat conservation. © 2024 The Authors. Restoration Ecology published by Wiley Periodicals LLC on behalf of Society for Ecological Restoration.